1996
DOI: 10.1121/1.414984
|View full text |Cite
|
Sign up to set email alerts
|

The effect of turbulent intermittency on scattering into an acoustic shadow zone

Abstract: Classical scattering theory predicts that the intensity of a saturated, scattered signal will have an exponential probability density function (pdf). However, the classical theory does not account for intermittency of the turbulence, which causes quantities such as the scattering cross section to vary in space and time. The classical theory can be modified to include intermittency by making the strength of the turbulence (i.e., the dissipation rate of turbulent kinetic energy) a local property of the scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…While the integral apparently has no analytical solution in this case, it can readily be performed numerically. Wilson et al (1996) applied this formulation to sound scattering into a shadow zone, and found good agreement with experimental data.…”
Section: B Intermittent Turbulencementioning
confidence: 67%
“…While the integral apparently has no analytical solution in this case, it can readily be performed numerically. Wilson et al (1996) applied this formulation to sound scattering into a shadow zone, and found good agreement with experimental data.…”
Section: B Intermittent Turbulencementioning
confidence: 67%
“…Notation has been simplified by the substitution L = 1/4 + Kt. As an elementary check of mathematical manipulations, it is easy to see from the above that the initial (t = 0) enstrophy distribution is indeed the square of c 0 (x) from equation (8).…”
Section: Transformation Of the N-s Equationmentioning
confidence: 93%
“…The FT of the velocity, vorticity, and second-term functions from equations (7), (8), and (10) are as follows:…”
Section: Transformation Of the N-s Equationmentioning
confidence: 99%
“…Small-scale intermittency can be relevant for electromagnetic and acoustic wave propagation (Tatarskii and Zavorotniy 1985) and therefore for the interpretation of measurements using radars, sodars, lidars, and laser scintillometers (Frehlich 1992). Wilson et al (1996) investigated the relevance of turbulence intermittency for acoustic wave propagation into a shadow zone.…”
Section: A Theory and Conceptsmentioning
confidence: 99%